Survival analysis and clinical abnormalities in cats with progressive or regressive feline leukemia virus (FeLV) infection in Brazil - Giovana Biezus; Thierry Grima de Cristo; Claudia Maria Flores Koehler; Flavia Yasmin de Quadros Kaveski; Thaís Sarria Viana Miranda; Paulo Eduardo Ferian; Renata Assis Casagrande (PLoS ONE, 2025)
This study aimed to characterize the clinical presentations and effects of progressive and regressive outcomes of feline leukemia virus (FeLV) infection on the life expectancy of cats. In total, 176 cats were selected: 116 with progressive infection (FeLV+P), 30 with regressive infection (FeLV+ R), and 30 FeLV-negative cats (Control). The cats underwent testing using ELISA to detect the FeLV p27 antigen and nested polymerase chain reaction to identify U3-LTR region and gag proviral DNA. The cats were clinically monitored until their death or for a period ranging 12–54 months. Survival analysis was performed using Kaplan–Meier analysis and Cox regression. The median survival time following FeLV diagnosis was 30 days for the FeLV+P group. The median survival time was not reached for the other groups. The cats’ health status (sick) at the time of inclusion in the study and the progression status of the FeLV infection led to a 4–5-fold increase in the Hazard Ratio (HR) for death in the general population. The primary causes of death among cats in the FeLV+P group were lymphoma, leukemia, anemia, and other diseases. In the FeLV+R group, the causes of death included leukemia, anemia, and other diseases. Progressive FeLV infection reduced life expectancy, whereas regressive FeLV infection had no direct impact on the survival curve.